Portuguese folklore sung by Malaccan Kristang groups and the issue of decreolization - Nunes, Mario (Journal of Modern Languages, 2017)
I do not wish to conduct a theoretical discussion of the notion of decreolization in this paper. Such work has been done by several authors who are much more knowledgeable in the field. Bickenon (1975) was probably the first, and we all know that decreolization is a central topic in his concept of the development of creoles. Based on his list of creole universals, I would like to focus on the influence these songs have had on Kristang. This paper does not pretend to be a complete and finite observation, as I have not done an analysis based on spontaneous discourse between Kristang speakers. My analysis is based on the Kristang version of two of the most popular Portuguese folk songs adopted in Malacca, "Tia Anica" and "Malhao, Malhao", as well as a recent recording of "Dia di San Pedro", a Kristang song (KS). In the transcription of the Kristang Version (KV) and the KS I have followed the orthography proposed by Joan Marbeck (1995).